Pengaruh Sertifikasi Halal dan Kualitas Produk Terhadap Keputusan Pembelian Produk Wardah di Desa Timbuseng Kab Takalar - Damayanti, Asruni; Muhammad Najib Kasim; Sri Wahyuni (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of halal certification and product quality on purchasing decisions for Wardah product in Timbuseng Village, Takalar Regency. The background of this study is based on the increasing public awareness of the importance of halal products, but their understanding of the value and function of halal certification and product quality in making purchasing decisions is still relatively low. The type of research conducted is quantitative with a descriptive and explanatory research approach. The population of this study were Muslim women aged 17-50 years who had purchased and used Wardah products, with a sample size of 212 respondents taken through purposive sampling techniques. Data collection was carried out through an online questionnaire and analyzed using multiple linear regression with the help of SPSS software version 25. The results of this study indicate that halal certification and product quality, both partially and simultaneously, have a positive and significant influence on purchasing decisions for Wardah products. These findings provide important implications for cosmetic manufacturers and halal certification institutions to increase consumer awareness, especially in rural areas.